COLLABORATIVE LEARNING TO IMPROVE PRESERVICE TEACHERS’ KNOWLEDGE ABOUT CHEMISTRY CONTENT IN THE AUTOMOTIVE VOCATIONAL CONTEXT - Antuni Wiyarsi; Sumar Hendayana; Harry Firman; Sjaeful Anwar (LPMPP Universitas Negeri Yogyakarta, 2015)
Abstract: This study was aimed to examine the effectiveness of collaborative problem-solving-based learning to improve knowledge about chemistry content in the automotive vocational context. The study design used was one-group pretest-posttest design and applied to Vocational Chemistry subjects. Data analysis was performed by using the normalized gain-test formula and t-test using SPSS software version 21. The findings showed that collaborative learning is effective to improve pre-service teachers’ knowledge about chemistry content of petroleum and polymer chemistry. The mastery level of basic knowledge about the petroleum and polymers is fairly good. However, the knowledge of the content of petroleum and polymer applications in the automotive field is not satisfactory. Although the application content knowledge increased with the moderate criterion for the application of petroleum and with the low criterion for polymer applications, the mastery level of pre-service teachers at the end of the course was still low. Factors that allegedly become the causes of the low mastery of application content knowledge are the characteristic factor of the content, conceptual learning difficulties and the experience factor. Keywords: content knowledge, chemistry in the vocational context, preservice chemistry teachers, petroleum, polymers PEMBELAJARAN KOLABORATIF UNTUK MENINGKATKAN PENGETAHUAN KONTEN KIMIA KONTEKS KEJURUAN OTOMOTIF CALON GURU KIMIA Abstrak: Penelitian ini bertujuan untuk mengkaji efektivitas pembelajaran kolaboratif berbasis pemecahan masalah dalam meningkatkan pengetahuan konten kimia konteks kejuruan otomotif. Desain penelitian yang digunakan adalah one group pretes-postes design dan diterapkan pada mata kuliah Kimia SMK. Analisis data dilakukan dengan uji t menggunakan software SPPS edisi 21 dengan menggunakan rumus gain-test yang dinormalisasi. Hasil penelitian menunjukkan bahwa pembelajaran kolaboratif efektif dalam meningkatkan pengetahuan konten minyak bumi dan polimer bagi mahasiswa calon guru kimia. Tingkat penguasaan pengetahuan dasar tentang minyak bumi dan polimer cukup baik. Namun, untuk pengetahuan konten aplikasi minyak bumi dan polimer dalam bidang otomotif belum memberikan hasil yang menggembirakan. Meskipun pengetahuan konten aplikasi tersebut meningkat dengan kriteria peningkatan sedang untuk aplikasi minyak bumi dan kriteria rendah untuk aplikasi polimer, tingkat penguasaan calon guru di akhir perkuliahan masih rendah. Faktor yang diduga menjadi penyebab rendahnya penguasaan pengetahuan konten aplikasi ini adalah faktor karakteristik konten, kesulitan belajar konseptual, dan faktor pengalaman. Kata Kunci: pengetahuan konten, kimia konteks kejuruan, calon guru kimia, minyak bumi, polimer